A new species of the Genus Pelodiscus Fitzinger, 1835 (Testudines: Trionychidae) from Huangshan, Anhui, China - Gong, Yan-An; Peng, Li-Fang; Huang, Song; Lin, Yan-Feng; Huang, Ru-Yi; Xu, Yu-Hao; Yang, Dian-Cheng; Nie, Liu-Wang (Zootaxa, 2021)
A new species of the soft-shelled turtle genus Pelodiscus is described based on seven specimens from Huangshan, southern Anhui Province, China. The new species, Pelodiscus huangshanensis sp. nov., is distinguished from other species in the genus Pelodiscus by the following characteristics: (1) Small size (maximum carapace length of 101.16 mm and maximum body length of 190 mm); (2) keel high; (3) tiny yellowish-white spots on the throat; (4) no black pinstripes around the eyes; (5) white longitudinal bands on both sides of the neck in juveniles, absent in adults; (6) plastron yellowish-white, and only a dark patch on each side of the armpit; (7) many tubercles on the dorsal surface, but indistinct in the center; and (8) entoplastron “⌒” shaped. The phylogenetic relationships of the species in Pelodiscus were reconstructed using the sequences of cytochrome b (cyt b) and NADH dehydrogenase subunit 4 (ND4) genes. The new species formed a monophyletic clade with strong support. The uncorrected pairwise distances between the new species and other representatives of Pelodiscus ranged from 5.4% to 9.2% for cyt b and 4.1% to 7.6% for ND4. The new species brings the number of species of the genus Pelodiscus to six; five species are distributed in China, with three species endemic to China.